Differential Diagnosis of Chest Pain - Lakshmanadoss, Umashankar (IntechOpen, 2020)
This book aims to provide an excellent overview of the differential diagnosis and approach to chest pain in various clinical settings. This book is divided into two sections including the introduction and the approach to chest pain. Our introductory chapter starts with the basic principles of statistics and its application in various diagnostic modalities of heart disease. Our authors present a nice approach to patients presenting with chest pain in various scenarios. We have also included a chapter describing GERD, which could present as chest pain and another chapter describing aortic dissection, which is a life-threatening disease presenting with chest pain. We hope that this book will serve as an accessible handbook on the differential diagnosis of chest pain.